Effect of Low Level Laser Therapy on Pain Reduction After Midpalatal Expansion in Rats - Ali Mohammad Hoseyni; Maryam Pirmoradian-Najafabadi; Sajjad Ashnagar; Hanieh Nokhbatolfoghahaei; Reza Fekrazad (Tehran University of Medical Sciences, 2016)
Objectives: The purpose of this experimental study was to evaluate the efficacy of low level laser therapy (LLLT) for pain reduction after midpalatal expansion in rats.   Materials and Methods: Sixty male Sprague six-week old rats weighing 180±10g were divided into seven groups (two experimental groups of 24 rats and one control group of 12 rats). The experimental groups were subjected to expansion with or without LLLT. The health status of each rat was monitored starting seven days prior to the experiment and evaluated by regular body weight monitoring during the study period. Diode laser with 810nm wavelength and 100 mw output power was used. Laser therapy and body weight monitoring were performed on days 0, 2, 4, 6, 8, 10, 12 and 14. The data were analyzed by One-way repeated measures ANOVA. Results: The body weight of the experimental groups significantly decreased in the first two days because of the pain and difficult nutrition with the new appliance. Within the next two days, the body weight of all rats increased but this increase was significantly higher in the irradiated compared to the non-irradiated group. This significant improvement continued until day 14 and then between days 14 and 30 the rats gained weight similarly in the irradiated and control groups. Conclusion: The study results showed that laser irradiated group continued to gain weight easier than the control group. This may be due to more efficient pain control due to laser irradiation after midpalatal expansion.